2009
DOI: 10.17221/125/2009-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

BVDV control program in Austria - is a monitoring of the BDV status in sheep in Austria necessary?

Abstract: ABSTRACT:In cattle referred to the Clinic of Ruminants at the University of Veterinary Medicine Vienna by local veterinarians from Lower Austria, the number of animals positive for antibodies against pestiviruses decreased from 11.9% in 2004 to 7.4% in 2007. In other Austrian regions the seroprevalence of 17.6% in 2004 dropped to 12.2% in 2007. The seroprevalence rates were considerably higher in older animals than in younger indicating a marked decrease of new infections (8.2% in < 1.5 years old animals, 6.8%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Thus, the mean BDV seroprevalence in pestivirus-antibody positive cattle of at least 6.7% with an increasing trend between 2012 and 2014 indicates that the serological surveillance by ELISA, which does not differentiate BVDV from BDV infections, might be critical. Even though discrimination by cross-SNT as described in this study is laborious, it adds to classical epidemiological investigations and allows the identification of possible sources of infection, which is of particular importance in the late phase of an eradication program [37, 48]. In summary, we determined for the first time the prevalence of BDV in pestivirus-positive cattle in Switzerland, and we provide strong evidence that common housing of cattle and sheep is the most significant risk factor for the interspecies transmission of BD virus from small ruminants to cattle.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the mean BDV seroprevalence in pestivirus-antibody positive cattle of at least 6.7% with an increasing trend between 2012 and 2014 indicates that the serological surveillance by ELISA, which does not differentiate BVDV from BDV infections, might be critical. Even though discrimination by cross-SNT as described in this study is laborious, it adds to classical epidemiological investigations and allows the identification of possible sources of infection, which is of particular importance in the late phase of an eradication program [37, 48]. In summary, we determined for the first time the prevalence of BDV in pestivirus-positive cattle in Switzerland, and we provide strong evidence that common housing of cattle and sheep is the most significant risk factor for the interspecies transmission of BD virus from small ruminants to cattle.…”
Section: Resultsmentioning
confidence: 99%
“…Virus transmission was described between cattle and both, sheep and goats ([19, 43, 44], and references therein). Natural infections of cattle with BDV were reported in England and Wales [45, 46], Austria [47, 48], Italy [49] and New Zealand [50]. Common housing of cattle with persistently infected sheep was the most important cause for seroconversions, and resulted in reduced fertility and abortions in pregnant cows [19, 44, 46].…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, all pestiviruses isolated from goats and sheep have been referred to as BDV, but genetic characteri-zation has shown that they can be infected with a wide range of pestiviruses including BDV, BVDV-1 and BVDV-2 (Pratelli et al, 2001;Giammarioli et al, 2015b). Equally, cases have reported of calves persistently infected with BDV (Krametter-Froetscher et al, 2009). Furthermore, recent studies showed that BDV strains have a genetic diversity greater than other pestivirus species (Giammarioli et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to what is observed in CSFV infections, ruminant pestiviruses show low species specificity in serological tests (Vilcek et al., ; Krametter‐Froetscher et al., ). In fact, BVDV‐1, BVDV‐2 and BDV are frequently detected either in cattle, sheep, goats and pigs.…”
Section: Introductionmentioning
confidence: 94%
“…Several epidemiological studies have shown that BDV genotypes can affect a wide range of ungulates, but generally, sheep seem naturally sensitive to pestivirus infection. BDV infection is globally distributed and was reported in different European countries such as Austria [ 30 , 32 , 36 , 46 , 79 , 80 ], France [ 4 , 5 , 14 , 41 , 81 ], Germany [ 12 , 39 , 44 , 82 , 83 ], Italy [ 15 , 16 , 31 , 66 , 76 , 77 , 78 , 79 ], the Netherlands [ 24 , 28 , 84 ], Slovakia [ 85 ], Spain [ 1 , 6 , 7 , 9 , 13 , 27 , 48 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 ], Switzerland [ 35 , 51 , 92 , 96 , 97 , 98 , 99 ], and the United Kingdom [ 3 , …”
Section: Global Distribution Of Bdv Genotypesmentioning
confidence: 99%